Clinical study on rabies prone animal bite - Hoque, Mohammad Mahfuzul; Akter, Farhana; Ahmed, BUM Wahid; E Alam, Sheikh Mohammad Noor; Amin, Robed; Faiz, MA (Bangladesh Journal of Medicine, 2018)
Introduction: Rabies is almost invariably fatal zoonotic disease, it can be prevent well with proper management of wound and rabies prophylaxis. This study aims to describe the pattern of rabies prone animal bite, to observe the trends of management and relationship with socioeconomic condition of victims. Method : This is an observational study. Data was collected from patients presenting with animal bite or attendants on structured case record form at Infectious Disease Hospital, Dhaka and emergency department of Mitford Hospital from 1st to 27th February 2010. Patients with category II &III bite were followed up 3 months over phone to observe the outcome. Results: A total 235 animal bite victims attending at Infectious Disease Hospital and Mitford Hospital were enrolled in study. Young patients, around 49.79% population within 18 years age group; male (82.98%) was more affected and mostly from low socioeconomic condition. Dog bite (91.06%) was predominant by stray dogs (94.89%) Exposure was mainly bite (83.82%), which were unprovoked (95.75%) and category – III(86.81%). Local wound care was minimal (wash with soap – 28.93%) and use of nerve tissue and cell culture vaccination was 81.70% and 18.29% respectively. Conclusion : Predominant rabies prone animal bite is stray dog. Victims after bite took ineffective nerve tissue vaccine while missing important rabies immunoglobulin due to economic constraints. The prevention of animal bite need to be addressed for prevention of rabies in Bangladesh. Bangladesh J Medicine Jan 2018; 29(1) : 26-30